An investigation on structural dynamic modification of a machine casing - Hanouf, Zahir; Abdelrahman, Ahmed; Ahmad, Kartini (Institute of Physics Publishing, 2022)
Investigation on structural dynamic characteristic is a crucial step in the noise, vibration and harshness (NVH) analysis in order to enhance the structural vibration, which subsequently contribute to improving the acoustical environment. The excitation of the structure can produce high vibration which could be transferred to the other parts of the body, then lead to high noise radiating components. Structural dynamic modification is one of the important techniques in the design of mechanical structures. It is an application of experimental modal analysis technique to investigate the effect of the physical and geometrical parameters on the dynamic properties of the structures such as frequencies and mode shapes. This paper investigates the dynamic properties of a machine casing structure which is extensively used in industrial applications. This investigation had successfully produced natural frequencies and their associated mode shapes of such open box for the original structure and modified structure. The study establishes the step-by-step procedures to carry out experimental modal analysis on the structures, using single input excitation and single output responses (SISO) technique. To ensure the validity of the results obtained an inverse method was done by fixing the response and moving the excitation. The results found were absolutely the same. Finally, comparison between results obtained from analysis showed significant differences on both frequencies and mode shapes.